Acute intracranial EBV and CMV infections after chemoimmunotherapy for EBV-associated nasopharyngeal carcinoma: a case report and literature review - Zhang, Zhenyu; Lin, Jiong; Song, Xinming; Yi, Xiaoqiong; Zhou, Hechao; Xu, Zumin (Frontiers in Oncology, 2025)
A 36-year-old male patient presented to our hospital complaining of epistaxis for 3 months and persistent headaches with facial numbness for 3 days. After a series of exams, he was diagnosed with nasopharyngeal carcinoma (T4N2M1, stage IVB, AJCC 8th), with a biopsy consistent with non-keratinizing squamous cell carcinoma, and received a combination therapy of gemcitabine, cisplatin, and tislelizumab. Following the first dose, headaches and facial numbness were relieved. On the third day, however, he developed recurrent fever, with a peak body temperature of 39.2 °C, and developed severe paroxysmal stabbing pain in the right frontal region suggestive of trigeminal neuralgia, along with numbness on the right face. We considered multiple possibilities and provided symptomatic treatments, but with poor efficacy. Subsequently, given the emergence of prominent neurological symptoms and fever, we proceeded with a lumbar puncture for cerebrospinal fluid (CSF) analysis. Metagenomic next-generation sequencing (mNGS) of CSF detected the presence of Epstein-Barr virus (EBV) and cytomegalovirus (CMV), and acute intracranial viral infections were considered. After treatment with ganciclovir, the patient’s body temperature returned to normal, and headaches and facial numbness were alleviated, and no pathogens were detected in a follow-up examination. We report a case of trigeminal neuralgia emerging post-chemoimmunotherapy, accompanied by CSF positivity for EBV and CMV, where antiviral intervention with ganciclovir resulted in significant symptom alleviation.